2024
DOI: 10.1186/s12888-024-05557-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in prevalence and associations between cognitive symptoms and suicidal ideation in patients with recurrent major depressive disorder: findings from the Chinese NSSD study

Ruizhi Mao,
Chenglei Wang,
Lvchun Cui
et al.

Abstract: Background This study aimed to explore gender differences in associations between cognitive symptoms and suicidal ideation (SI) among patients with recurrent major depressive disorder (MDD). Methods We recruited 1222 patients with recurrent MDD from the National Survey on Symptomatology of Depression (NSSD), a survey designed to investigate the symptoms experienced during current major depressive episodes in China. A four-point Likert questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The genetic mechanisms of this phenomenon are being studied [ 68 , 69 ]. At the same time, in most studies [ 55 , 70 , 71 , 72 , 73 ], with the exception of a few [ 74 ], the influence of gender on cognitive decline was not revealed. In contrast, our study revealed a significant influence of gender on cognitive impairment in PCD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic mechanisms of this phenomenon are being studied [ 68 , 69 ]. At the same time, in most studies [ 55 , 70 , 71 , 72 , 73 ], with the exception of a few [ 74 ], the influence of gender on cognitive decline was not revealed. In contrast, our study revealed a significant influence of gender on cognitive impairment in PCD patients.…”
Section: Discussionmentioning
confidence: 99%